The use Of Context, Input, Process, Product (CIPP) Evaluation Model in the Duha Prayer Habituation Program at Integrated Islamic Elementary School (SD IT) Rocha Indonesia Bandung - Afifah, Annisa Nur; Kholilah, Lilis; Nengsih, Wida; Yani, Ahmad (The Future of Education Journal, 2024)
The formation of good character has become one of the goals that must be achieved in education. Character, which is part of affective competence, is sought to be achieved both in classroom learning activities and outside the classroom in the form of programs. Many educational institutions conduct character development through programs; however, they do not receive serious attention because they are allowed to run without clear evaluation. This research aims to conduct an evaluation of the character development program implemented at SD IT Rocha Indonesia School in Bandung Regency. The research approach is descriptive qualitative with data collection techniques of observation and interviews. The data were analyzed by performing data reduction, data presentation, and drawing conclusions. The research results show that the CIPP evaluation model provides a clear picture of the habituation of dhuha prayers at SD IT Rocha Indonesia, Bandung Regency, both in terms of its strengths and weaknesses as material for subsequent decision-making.